Digital Culture, Global Influences and Cultural Hybridization - Magar , Deepak Pun (AMC Journal (Dhangadhi), 2026)
The rapid expansion of digital technologies has transformed cultural production, circulation and consumption. It has created new spaces for creativity, interaction and identity construction. This study examines the interrelationships of digital culture, global influence and cultural hybridization. It sheds light on how local communities engage with global cultural flows while preserving and reinterpreting their own traditions. Using a conceptual and descriptive methodology based entirely on secondary sources, the research analyses scholarly literature, policy documents and reports published between 2000 and 2025. The study focuses on themes such as global cultural penetration, hybrid cultural practices, identity negotiations and the socio-economic and technological factors that shape digital engagement. The findings indicate that digital culture facilitates cultural exchange and hybridization. It produces new forms of music, language, fashion, storytelling and social practices. However, participation in these processes is uneven. Influenced by access to technology, digital literacy and socio-economic status. Hybrid cultural practices reflect both continuity and change. It illustrates human creativity and adaptability in the digital age. The study concludes that inclusive policies, digital literacy initiatives and equal access to digital platforms are needed to support cultural innovation, preserve local heritage and empower communities to navigate global impacts responsibly.